Detection of Burnt Areas by Remote Sensing Techniques: Antalya Manavgat Forest Fire - Orhun Soydan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the forest fire that occurred in Manavgat district of Antalya on 28 July 2021 and lasted for 15 days was analysed by remote sensing techniques using Landsat 8 satellite images. Satellite images of the study area dated July 2021 before the forest fire and August 2021 after the forest fire were obtained. Burnt areas were identified using data’s such as Normalized Burned Ratio (NBR) and Normalized Vegetation Index (NDVI) indices and Difference Normalized Burned Ratio (DNBR) and Difference Normalized Vegetation Index obtained by using the differences of these indices. The maximum similarity algorithm of pixel-based controlled classification was also applied to the data set. The area destroyed by burning after the forest fire was tried to be calculated with these two indexes. It was investigated whether the results of three different methods were compatible and consistent with the results of the General Directorate of Forestry. Although there are differences between the results, it was determined that the selected method and the materials used were suitable for such studies.